Angiotensin II increases matrix metalloproteinase 2 expression in human aortic smooth muscle cells via AT1R and ERK1/2. (December 2015) - Wang, Chunmao; Qian, Xiangyang; Sun, Xiaogang; Chang, Qian
Increased levels of angiotensin II (Ang II) and activated matrix metalloproteinase 2 (MMP-2) produced by human aortic smooth muscle cells (human ASMCs) have recently been implicated in the pathogenesis of thoracic aortic aneurysm (TAA). Additionally, angiotensin II type 1 receptor (AT1R)-mediated extracellular signal-regulated kinase (ERK)1/2 activation contributes to TAA development in Marfan Syndrome. However, there is scant data regarding the relationship between Ang II and MMP-2 expression in human ASMCs. Therefore, we investigated the effect of Ang II on MMP-2 expression in human ASMCs and used Western blotting to identify the Ang II receptors and intracellular signaling pathways involved. Reverse transcription polymerase chain reaction (RT-PCR) and immunofluorescence data demonstrated that Ang II receptors were expressed on human ASMCs. Additionally, Ang II increased the expression of Ang II type 2 receptor (AT2R) but not AT1R at both the transcriptional and translational levels. Furthermore, Western blotting showed that Ang II increased MMP-2 expression in human ASMCs in a dose- and time-dependent manner. This response was completely inhibited by the AT1R inhibitor candesartan but not by the AT2R blocker PD123319. In addition, Ang II–induced upregulation of MMP-2 was mediated by the activation of ERK1/2, whereas p38 mitogen-activated protein kinase (p38 MAPK) and c-Jun N-terminal kinase (JNK) had no effect on this process. In conclusion, these results indicate that Ang II can increase the expression of MMP-2 via AT1 receptor and ERK1/2 signaling pathways in human ASMCs and suggest that antagonists of AT1R and ERK1/2 may be useful for treating TAAs.